Political Connections and Income Smoothing: Does Ownership Structure Matter? - Imanuela Wahyu Krisdina; Yeterina Nugrahanti (Jurnal Akuntansi dan Keuangan, 2025)
This study aims to examine the effect of political connections on income smoothing. In addition, this study seeks to investigate whether ownership structure, as operationalized by institutional and managerial ownership, strengthens or weakens the relationship between political connections and income smoothing. This study uses political connection as the independent variable, income smoothing as the dependent variable, and institutional ownership and managerial ownership as the moderating variables. This study uses secondary data from publicly listed Indonesian energy-sector firms’ annual reports for 2020-2022. The logistic regression and Moderated Regression Analysis (MRA) reveal that political connections positively affect income smoothing. Additionally, as a moderating variable, institutional (managerial) ownership mitigates (strengthens) the effect of political connections on income smoothing